EXPLOITATION RELIABILITY OF RECUPERATORS - A. M. Selutin; V. A. Zharanov; A. V. Tkachenko (Литьë и металлургия)
The investigations and experience of implementation of constructions, that provide increase of gas-tightness of heat-exchangers, are described in the article. The given variants of compensators of different types allow to increase the reliability of operation of systems of the fuel furnaces waste flue gases heat using.